EFL TEACHERS’ CAPABILITY AND BARRIERS IN USING INFORMATION AND COMMUNICATION TECHNOLOGY (ICT) - Harli Zadtyi; Ismail Petrus; Machdalena Vianty (English Review: Journal of English Education, 2021)
Integrating and developing ICT for the school has become an important facet and conferred a more robust pattern to get the new teaching and learning models. The combination of ICT has several benefits to form a context for teaching and learning English skills. In this pandemic situation, teachers should use kind of ICT tools for online teaching. Supported this necessity, there must be problems faced by the teacher in the access of ICT. Studying the teachers' capability and barriers in education will help teachers become successful technology adopters in the future. This study applied a qualitative descriptive research design conducted through questionnaires, observation, and interviews. The result of the questionnaire, interview, and observation was described. Participants were EFL teachers from senior-high-schools in Sanga desa. The study findings Teachers category good in capability and the main barriers faced by teachers were lack of facilities, time, training, and internet problem. The research has the purpose of exploring teachers' capability and the barriers they face to improve the quality of ICT use in teaching English in the future.